Change and Adaptation: Historic School Buildings and the impact of Conservation on Cultural Significance - Aleixo, Sofia (2020)
Changes in education reflect societal developments, such as social and economic demands, environmental constraints and technological developments. As a result, the educational environments are required to change and adapt. Additionally, the fact that educational architecture is in physical decay and in lack of physical conditions to support contemporary educational methods, raise questions on the preservation of authenticity and existing cultural values while providing new spaces, with new architectural and educational values. At the turn of the 20th century, the first school buildings purposefully designed for secondary education offered a solution for the then new function integrating architectural and educational theory. In the dawn of the 21st century, several countries undertook interventions in school architecture bringing challenges to architects in the development of design strategies and solutions to new architectural requirements and new education theory. Furthermore, architects need to consider the impact of their adaptation and expansion design on the local community as these heritage environments are places of educational, social, historic and architectural significance. This paper brings to the debate a discussion on the challenges facing educational architecture conservation by exploring recent experiences in Portugal. Although the aim to update all historic Lyceums (secondary schools) to current educational standards and needs is still to be achieved, a qualitative research approach was undertaken using a case study strategy to explore the interventions finished by 2010. Open ended questionnaires, interviews, and particularly the analysis of the designed projects and the historic buildings themselves, on site visits, were applied. Results showed that strategies of conservation and extension of the historic Lyceums, retained these historic school’s cultural significance by applying a strategy of minimum intervention, at material and at space use level. Therefore, results support the argument that values ascribed to historic schools are closely related to the place’s authenticity contributing to raise awareness about the architectural and educational heritage of these spaces. Finally, this paper recommends architectural conservation of historic places of education to establish a preliminary understanding of the architecture and education devices that are responsible for the continuity of cultural values in order to avoid blind and meaningless conservation actions.